Current tools for diagnosis, handling and control of dental caries. Part II. A literature review - Jara Porroa, Jackeline Jajaira (2020)
The International System of Classification and Management of Caries (ICCMS) is a comprehensive set of clinical protocols aimed at providing a better approach to the diagnosis, treatment and prevention of dental caries. Modification of risk factors, treatment of teeth with active caries lesions and the preservation of the structure of dental enamel in order to restore tooth structure only when necessary are ideal approaches that odontopediatricians should incorporate into daily practice. The objective of this study was to present the current diagnostic tools to improve the decisionmaking when selecting treatment plans and provide more individualized care to each patient.